Dynamics of changes in physical and psychoemotional condition of women under the influence of swimming occupations - Liliya Sheyko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to reveal influence of occupations in improving swimming on the psychoemotional sphere and the general indicators of women's health. Material & Methods: 52 women at the age of 25-40 years have participated in research. Data collection was carried out in recreational groups of аuthor's swimming school of Y. Bliznuk and the pool "Pioneer". Methods applied: poll, testing, instrumental methods of cardiovascular system and anthropometry research; indicators of physical, mental and social health were determined by S. Stepanov's technique; assessment of health, activities and moods was carried out by means of questionnaire "SAN". The obtained quantitative data were processed by methods of mathematical statistics. Results: conducted research demonstrates that improving swimming occupations cause positive changes in physical development, physical fitness and psychoemotional condition of women; improvement of indicators of physical and psycho-emotional state is most explicitly revealed after 2 years of occupations. Conclusions: it is established that occupations in improving swimming for 2 years have positively affected on the psycho-emotional sphere and the general indicators of women's health.